Who leads the IoT ecosystem? a Meta-frontier Approach - Hosoo Cho; Min Ho Ryu (International Telecommunications Society (ITS), 2019)
As 5G has recently been commercialized, IoT ecosystem is rapidly growing. There are variety of participants in IoT ecosystem and they continue to innovate in their own way. This paper divided participants of IoT ecosystem into four sub-industries: service, network, platform, and device. This paper applies stochastic frontier analysis (SFA) and compare the efficiency among these sub-industries, which give us information who leads innovation in the sub-industry or between the sub-industries. After analyzing the financial data of Korean IoT companies from 2008 to 2018, this paper show that platform industry had led the innovation of IoT ecosystem in the early stage (until 2007) and after then, network and device industries have led the innovation, while service industry lags relatively behind other industries during the period. Moreover, the empirical findings collectively indicate that meta-frontier index values (TE, TGR and TE*) have all been continuously decreasing, which means that some of highly efficient companies in the IoT ecosystem have consistently maintained their dominance.
Keywords: 330; IoT ecosystem; stochastic frontier analysis; meta-frontier analysis; IoT industry in Korea; innovation